2022
DOI: 10.1177/11297298211068302
|View full text |Cite
|
Sign up to set email alerts
|

The intracavitary ECG method for tip location of ultrasound-guided centrally inserted central catheter in neonates

Abstract: Background: The correct position of the tip of a central venous access device is important in all patients, and especially in neonates. The traditional method of tip location (approximated intra-procedural length estimation + post procedural chest X-ray) is currently considered inaccurate and not cost-effective by most recent guidelines, which recommend the adoption of tip location by intracavitary electrocardiography (IC-ECG) whenever possible. Methods: This study prospectively investigated the applicability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
(87 reference statements)
0
5
0
1
Order By: Relevance
“…16 We had chosen ultrasound-based tip location because is particularly easy in neonates, but the intracavitary ECG technique is also an excellent option for tip location in neonates. 17 In all patients, the tip position of CICC was the upper third of the RA. The exit site and the skin incisions were sealed with cyanoacrylate glue in all patients.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…16 We had chosen ultrasound-based tip location because is particularly easy in neonates, but the intracavitary ECG technique is also an excellent option for tip location in neonates. 17 In all patients, the tip position of CICC was the upper third of the RA. The exit site and the skin incisions were sealed with cyanoacrylate glue in all patients.…”
Section: Resultsmentioning
confidence: 95%
“…Ultrasound-guided CICC implantation in the newborn is recommended by international guidelines, 1,19,20 and ultrasound control of the tip position according to the most up-to-date guidelines does not require chest radiographs—which is far less accurate- avoiding ionizing radiation to the newborn. 17,19,20…”
Section: Discussionmentioning
confidence: 99%
“…46 O ECG se mostra com uma tecnologia adequada para a colocação guiada do PICC e para a verificação do posicionamento da ponta do cateter, com precisão de 100%. 62 O procedimento tem como vantagens: a precisão de ser em tempo real, evitar a radiação, menor tempo para inserção, ser um procedimento simples que requer a habilidade do profissional.…”
Section: Resultsunclassified
“…Several clinical studies have demonstrated that IC-ECG is more accurate than radiological methods when compared to the TEE [13][14][15] ; the method is also easy and inexpensive, and it can be applied in adults, 6 in children 16 and in neonates. 17 The other main intra-procedural method for tip location is TTE: ultrasound-based tip location is based on the ultrasound visualization of the right atrium using a convex or a sectorial probe, adopting different acoustic windows (the subxiphoid longitudinal view, the subxiphoid bi-caval view, and the apical view); this method of tip location has been standardized in adults, 7 in children 18 and in neonates. 19 Tip location of FICCs still remains a matter of debate.…”
Section: Discussionmentioning
confidence: 99%